Sustainable WEF Nexus Management: A Conceptual Framework to Integrate Models of Social, Economic, Policy, and Institutional Developments - Akinsete, Ebun; Koundouri, Phoebe; Kartala, Xanthi; Englezos, Nikos; Lautze, Jonathan; Yihdego, Zeray; Gibson, Julie; Scholz, Geeske; van Bers, Caroline; Sodoge, Jan (Frontiers in Water, 2022)
Rapid population growth and increased rates of economic growth around the globe are placing valuable natural resources, water in particular, under unprecedented stress; in turn driving the pursuit of innovative tools to support integrated Water-Energy-Food (WEF) nexus management. This paper presents a framework for the integrated management of the WEF nexus, which brings together four separate models that address the less well-examined socio-anthropological aspects of the nexus. The proposed framework provides insight into the human element as part of the wider ecosystem in terms of socio-cultural and economic activities, the laws and policies that govern these activities, as well as their potential socio-economic impacts and consequences. This paper outlines each individual model, before going on to present a conceptual framework for the integration of the various models for the purpose of supporting more robust decision-making. The framework, which is grounded in systems thinking, adopts the principles of sustainable development as structural foci in order to position the various models in relation to one another; harmonizing their inputs as well as outputs.